Kata Motivasi Belajar Dan Paradigma Belajar Dalam Hadist Nabi Shallallahu ‘Alaihi Wa Sallam - Hayati, Mufidah; Hafizh, Muhammad; Charles (Jurnal Multidisiplin Indonesia, 2023)
In Islam, intention and motivation have an important role in assessing the quality of a charity. Even the acceptance or rejection of one's good deeds in the sight of Allah SWT is largely determined by his intentions and motivation. Learning activities (at-ta'allum) are part of the good deeds that are obligatory for every Muslim in order to acquire knowledge (al-'ilm) and knowledge (al-ma'rifah). Because of the importance of learning activities, one's intentions and motivation in learning and seeking knowledge get special attention in Islam, especially those conveyed through the hadiths of the Prophet Muhammad. This paper intends to describe the concept of learning motivation according to the hadiths of the Prophet SAW and analyze it with the theories of experts on learning motivation and will try to formulate the meaning of learning from an Islamic perspective, examine learning theories from a psychological and Islamic perspective, and find equivalent learning theories. in the Al-Quran and Hadith. From the results of the research conducted by the authors, it was concluded that the two hadiths have hadith status as shahih li ghairi or hasan-shahih, so that both of them can be used as a basis for studying motivation in the As-Sunnah perspective. Learning motivation according to the hadiths can be divided into two types, namely: spiritual motivation and worldly motivation. These two types of motivation can stand alone or contradict each other and can also be positively correlated or merge into mundane-ukhrawi motivations.